PIE to be shared - Zailin Shah, Yusoff (Pusat Bahasa Moden dan Sains Kemanusiaan, 2009)
12 Nov 2009. The Preparatory Intensive Program (PIE) offered by CMLHS is tailored to cater for international students about to embark on their undergraduate study.